Vincetoxicum luridum (Asclepiadeae, Asclepiadoideae, Apocynaceae), a new and long misunderstood endemic species from Balochistan, Pakistan - Shah, Sayed A.; Sultan, Amir; Wen, Jun; Nisa, Surat U.; Su, Xu; Iqbal, Javed; Mumtaz, Abdul S. (Phytotaxa, 2018)
We here describe a new species, Vincetoxicum luridum, from South West Balochistan. Scanning electron microscopy (SEM) of leaves and seeds, palynology and chorology support the recognition of V. luridum. The lurid appearance, dense pubescence and ovate corona lobes readily distinguish V. luridum from the closely related species V. stocksii which is endemic to North East Balochistan. We illustrate V. luridum, and confirm the significance of corona morphology for classification of Vincetoxicum in Pakistan. Presently, the V. arnottianum complex comprise four species with purple flowers viz., V. arnottianum, V. sakesarense, V. luridum and V. stocksii. In this study we also present the geographic distribution and a taxonomic key to the taxa of V. arnottianum complex.